Teachers' organizational commitment in schools: the influence of work culture and servant leadership - Solihatun Solihatun; Yulinda Siregar; Sahat T. Simorangkir; Djoni Aminudin; Burju Ruth (Jurnal Konseling dan Pendidikan, 2026)
In the context of increasingly complex educational demands, strengthening teachers’ organizational commitment has become a critical issue in improving school effectiveness. While prior studies highlight organizational culture and leadership as key determinants, empirical findings remain inconsistent, indicating the need for further investigation in specific educational contexts. Drawing on organizational and servant leadership theories, this study examines the influence of work culture and servant leadership on teachers’ organizational commitment. This study employed a quantitative approach with a cross-sectional survey design involving 180 teachers selected through proportional random sampling. Data were collected using validated and reliable Likert-scale questionnaires and analyzed using descriptive and inferential statistical techniques. The findings indicate that servant leadership plays a more significant role in influencing teachers’ organizational commitment, while work culture does not show a meaningful effect. Overall, the results suggest that teachers’ organizational commitment is shaped by complex and context-dependent factors. This study highlights the importance of integrating psychological and professional aspects in efforts to enhance teacher commitment.